Adjustment of children in joint custody and associated variables: A systematic review. Issue 4 (2nd October 2019) - Baude, Amandine; Drapeau, Sylvie; Lachance, Véronique; Ivers, Hans
Abstract: This systematic review examines studies conducted since the year 2000 on the adjustment of children (0-18 years) in joint custody (30/70%) and on the associated family factors (i.e., parenting and interparental conflict). Studies were extracted following PRISMA. Sixteen quantitative studies met the inclusion criteria. Fourteen assessed internalizing adjustment and 10 examined externalizing adjustment. Only 2 were rated as having high quality. Limitations included cross-sectional design, reliance in single informant, failure to adjust for important characteristics and no theoretical approach. The results show that the adjustment level of children in joint custody is as good, if not better, than that of those in sole custody. It also shows however that interparental conflict, parental practices, and the parents' mental health generally play a more influential role. In regard to conflictual contexts, studies are beginning to identify, particularly in joint custody, risk factors such as strict arrangements and concerns about the children's safety.